An ontology for biological function based on molecular interactions - Karp, Peter D. (Bioinformatics, 2000)
Motivations: A number of important bioinformatics computations involve computing with function: executing computational operations whose inputs or outputs are descriptions of the functions of biomolecules. Examples include performing functional queries to sequence and pathway databases, and determining functional equality to evaluate algorithms that predict function from sequence. A prerequisite to computing with function is the existence of an ontology that provides a structured semantic encoding of function. Functional bioinformatics is an emerging subfield of bioinformatics that is concerned with developing ontologies and algorithms for computing with biological function. Results: The article explores the notion of computing with function, and explains the importance of ontologies of function to bioinformatics. The functional ontology developed for the EcoCyc database is presented. This ontology can encode a diverse array of biochemical processes, including enzymatic reactions involving small-molecule substrates and macromolecular substrates, signal-transduction processes, transport events, and mechanisms of regulation of gene expression. The ontology is validated through its use to express complex functional queries for the EcoCyc DB. Contact: pkarp@ai.sri.com